2017
DOI: 10.5301/ijbm.5000284
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM-Expressing Circulating Tumor Cells in Colorectal Cancer

Abstract: This is the first demonstration that the low sensitivity of CellSearch® to detect CTCs in colorectal cancer patients is not due to the lack of EpCAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
1
29
0
4
Order By: Relevance
“…EpCAM low CTCs was not signi cantly associated with prognosis of patients, contrary to the presence of ≥5 EpCAM high . Additionally, previous study also indicated that EpCAM high CTCs from colorectal cancer approximately account for 89% (39), which indicates the numbers of CTCs detected with CellSearch system were more than the missed EpCAM low CTCs, and correspondingly the signi cance of EpCAM high CTCs were higher. Collectively, these studies all suggested that although CTCs with a mesenchymal phenotype may not be detected by the CellSearch system, obvious signi cance of EpCAM low CTCs in predicating prognosis in cancer patients was not indicated.…”
Section: Discussionmentioning
confidence: 88%
“…EpCAM low CTCs was not signi cantly associated with prognosis of patients, contrary to the presence of ≥5 EpCAM high . Additionally, previous study also indicated that EpCAM high CTCs from colorectal cancer approximately account for 89% (39), which indicates the numbers of CTCs detected with CellSearch system were more than the missed EpCAM low CTCs, and correspondingly the signi cance of EpCAM high CTCs were higher. Collectively, these studies all suggested that although CTCs with a mesenchymal phenotype may not be detected by the CellSearch system, obvious signi cance of EpCAM low CTCs in predicating prognosis in cancer patients was not indicated.…”
Section: Discussionmentioning
confidence: 88%
“…Depletion of leukocytes. Leukocyte depletion was performed using Dynabeads CD45 (Invitrogen; Thermo Fisher Scientific, Inc.) in order to enrich CTCs from whole blood, following the manufacturer's instructions, as previously described (33). Each blood sample was incubated with Dynabeads (Invitrogen; Thermo Fisher Scientific, Inc.) for 30 min at 2˚C with gentle tilting rotation.…”
Section: Methodsmentioning
confidence: 99%
“…53 Quantification of CTCs has been validated for colorectal cancer prognosis, [54][55][56] and increasingly sensitive approaches are being developed for CTC detection in patients with colorectal cancer. 57,58 It is anticipated that such techniques may be used for more sophisticated analysis based on specific markers, such as detection of the KRAS mutation in peripheral blood CTCs, which has been associated with response to cetuximab plus chemotherapy, 59 or FAM172A expression in mesenchymal CTCs, which may be predictive of high-risk stage II colorectal cancer. 60 CTC count has been reported to be predictive of metastasis in patients with gastric cancer, 54 which is a particularly aggressive cancer that is common in Asia, Eastern Europe, and Central and South America.…”
Section: Ctcs and Gastrointestinal Tract Cancersmentioning
confidence: 99%
“…It is thought that monitoring for CTCs in patients with early‐stage colorectal cancer before and after surgery could help to identify patients who are at risk of disease recurrence and therefore are likely to benefit from adjuvant therapy . Quantification of CTCs has been validated for colorectal cancer prognosis, and increasingly sensitive approaches are being developed for CTC detection in patients with colorectal cancer . It is anticipated that such techniques may be used for more sophisticated analysis based on specific markers, such as detection of the KRAS mutation in peripheral blood CTCs, which has been associated with response to cetuximab plus chemotherapy, or FAM172A expression in mesenchymal CTCs, which may be predictive of high‐risk stage II colorectal cancer …”
Section: Introductionmentioning
confidence: 99%